On-farm insights in the South American Gran Chaco reveal the importance of soil organic matter and crop management decisions for boosting maize yields - Madias, Andrés; Simon, Carlos Gabriel; Stahringer, Nicolás I.; Borrás, Lucas; Rubio, Gerardo; Gambin, Brenda L. (Elsevier, 2025)
Soybean monoculture is widespread across recently deforested areas in South America, leading to a decline in soil organic matter (SOM) and compromising the sustainability of the cropping system. Introducing cereals like maize into the crop rotation is necessary, but proper management knowledge to maximize its yield and profitability is needed. Our objectives were to quantify the impact of management and environmental variables influencing maize yield and estimate the potential to increase attainable yields in recently deforested fields of South American Gran Chaco. The analysis included a total of 62 on-farm trials across multiple environments, each including 9–28 hybrids. The mean site yields ranged from 2235 to 11141 kg ha−1. Using linear mixed models, we identified and tested a model with key management and environmental variables explaining yield variation. We used this model to estimate attainable yields across the region. Nitrogen availability, sowing date, and hybrid type (temperate or sub-tropical) were the most important management variables to predict yield (relative importance ≥ 0.80). Soil organic matter and soil water availability at sowing were the most important environmental yield predictors (relative importance of 0.71 and 0.66, respectively). The best model, tested against an independent dataset (n = 34 trials; RMSE=1722 kg ha−1; RRMSE=21 %) confirmed the influence of defined predictors. Our findings demonstrate that simple management adjustments can boost yields by ∼20 % (∼1500 kg ha−1). In this recently deforested region, the decline in SOM and its negative impact on yields highlight the importance of crop management strategies and policies aimed at improving current cropping systems.